Analytical solution to axisymmetric consolidation in unsaturated soils with linearly depth-dependent initial conditions. (April 2016) - Ho, Liem; Fatahi, Behzad; Khabbaz, Hadi
Abstract: This paper introduces an analytical solution for the axisymmetric consolidation of unsaturated soils subjected to constant external loading. The analytical procedure employs variables separation and Laplace transformation techniques while capturing the uniform and linear initial excess pore pressure distributions with depth. Excess pore-air and pore-water pressures as functions of time, radial and vertical flows are determined using Laplace transforms, Fourier Bessel and sine series, respectively. In this study, the consolidation behavior, in terms of changes in excess pore-air and pore-water pressures and the average degree of consolidation, are investigated against the air to water permeability ratio. The effects of radial distance from the drain well on the dissipation rate are likewise highlighted in worked examples. Excess pore pressure isochrones and the matric suction varying with time are also presented.